Geo-economic Dynamics of the Industry in Ampére, Brazil: evolution and consolidation (Terr@ Plural, 2023)
This paper aims to understand the geo-economic dynamics of industry in Ampére and the main characteristics and determining factors of this process, understanding it not as an isolated fact, but connected to the regional and national context. The Socio-Spatial Formation (SSF) category of analysis was considered, along with a bibliographical and documentary review and fieldwork. The SEF of the southwest of Paraná, the mesoregion of the study area, was developed based on smallscale commercial production and Ampére has a significant manufacturing sector, standing out in two sectors of the transformation industry (clothing and furniture production). In the southwest of Paraná, it is the main hub for these sectors; in the state of Paraná, it is among the 10 main hubs and in Brazil, it is the 65th largest employer in the clothing sector and the 43rd in the furniture industry. This position of industrial importance is the result of a combination of private initiatives based on small-scale commercial production, municipal public support, as well as federal policies and programs that boosted the domestic market during the 2000s.
Keywords: Industrialization; Socio-Spatial Formation; Regional development; small cities; Spatial dynamics